2018
DOI: 10.14715/cmb/2018.64.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of 3β-HSD and mlncRNAs in response to abiotic stresses in Digitalis nervosa

Abstract: Digitalis nervosa is an important medicinal plant species belonging to the family of Scrophulariaceae that has the potential to be used for heart failure.3β-hydroxysteroid dehydrogenase (3β-HSD) is a key gene in the biosynthesis of cardenolides for making digitalis effective compounds, hence identification of this gene is important for genetic engineering purposes towards increasing the yield of cardiac glycosides. In addition, mRNA-like non-coding RNAs (mlncRNAs), a class of long non coding RNAs, play key rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…It indicated the adjacent relationship between 3β-HSD and three mlncRNAs through an unknown mechanism. Also, it revealed that the possible accumulation of mentioned transcripts in the aerial parts of plants was associated with secondary metabolites biosynthesis site [88]. Due to the fact that the expression levels of three mlncRNAs and 3β-HSD under stress conditions are similar and decreased, mlncRNAs are more possibly stress-responsive [88].…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…It indicated the adjacent relationship between 3β-HSD and three mlncRNAs through an unknown mechanism. Also, it revealed that the possible accumulation of mentioned transcripts in the aerial parts of plants was associated with secondary metabolites biosynthesis site [88]. Due to the fact that the expression levels of three mlncRNAs and 3β-HSD under stress conditions are similar and decreased, mlncRNAs are more possibly stress-responsive [88].…”
Section: Plos Onementioning
confidence: 99%
“…Identification of mlncRNAs. The mlncRNAs are considered as a subset of long noncoding RNAs (lncRNAs) and a new group of regulatory elements [88], which can be spliced, capped and polyadenylated [43]. In plants, mlncRNAs have regulatory roles in phosphate-starvation response, gender specific expression, nodulation, development, and response to hormones; also, they can affect cellular activity through specific sequences and RNA-folding structures [89].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation